Advantages of MSMEs Post Covid-19 Through Product Design, Product Quality and Price Toward Purchase Decisions at The Tempe Harber (HB) Factory - Irna Sari Sihombing; P. Pristiyono; Abd. Halim (PT Mattawang Mediatama Solution, 2022)
This study aims to determine the effect of product design (X1) on the advantages of MSMEs (Z), to determine product quality (X2) to the advantages of MSMEs (Z), and to determine the price (X3) to the advantages of MSMEs (Z), to determine product design. (X1) on purchasing decisions (Y), to determine product quality (X2) on purchasing decisions (Y), and to determine price (X3) on purchasing decisions (Y), to determine purchasing decisions (Y) on the advantages of SMEs (Z). This study uses quantitative methods to determine the effect of independent variables (product design, product quality and price) on the dependent variable (purchase decisions) through the intervening variable (MSME advantages). The decision to purchase the tempe harber (HB) factory on Jalan Aek Tapa A in this study was that the population was unknown, while the sample was taken using the Lemeshow formula using a 90% ability level and 10% error margin. The results of the respondents obtained were 96 decision makers in this study. The collection technique is by distributing a questionnaire (questionnaire) using google form. This research uses data analysis method using PLS (Partial least square) which is run using smartPLS 3 software. The collection technique is by distributing a questionnaire (questionnaire) using google form. This research uses data analysis method using PLS (Partial least square) which is run using smartPLS 3 software. The collection technique is by distributing a questionnaire (questionnaire) using google form. This research uses data analysis method using PLS (Partial least square) which is run using smartPLS 3 software. The results of the hypothesis which indicate that product design, product quality and price on purchasing decisions are significant, that the T-Statistic value is > 1.96 so that the P-Values ​​are <0.05. Likewise, the results of the hypothesis that the price and purchasing decisions on the advantages of MSMEs are also significant with a T-Statistic value> 1.96 and a P-Values ​​value <0.05. The results of the product design hypothesis and product quality are stated to be insignificant but have a positive effect because the T-Statistic value is > 1.96 and the P-Values ​​value is > 0.05. The results of the R-Square test can be seen that the purchasing decision has the ability to product design, product quality and price with a value of 0.626, where the purchase decision is 62.6% which is stated that it belongs to the medium category.